How organizational research can avoid the pitfalls of a co-optation perspective - Striedinger, Angelika (My University, 2017)
The concept of co-optation offers vocabulary to discuss how concerns and demands of feminist movements are transformed on their way to, and within, mainstream organizations and policymaking. However, applications of this concept can have problematic implications, failing to grasp the complexity of social change efforts and contributing to divisions, rather than alliances, between different groups that work and fight for gender equality. This article argues that conceptual tools from organizational institutionalism can help to avoid these pitfalls by capturing the ambivalence of organizational change initiatives, and allowing us to identify not only counterintentional effects, but also subtle and unexpected opportunities of organizational gender equality work. I illustrate my arguments with empirical examples from research on gender equality work in Austrian universities.
analyzing gender equality work in Austrian universities with organizational institutionalism
Keywords: Gender; Institutionalisierung; Feminismus; Organisation; Soziale Bewegung; Universität; 320 Politikwissenschaft; Co-optation; Organizational institutionalism; Gender equality; Universities